El proceso político de las iniciativas legislativas climáticas en el Perú: la tortuosa travesía de la Ley Marco sobre Cambio Climático (2008-2018) - Bravo Alarcón, Fernando (2022)
This article seeks to contradict the assumption that environmental and climate issues are subordinated to the economic growth agenda in public policy and legislative decisions. On the contrary, it proposes that certain political conditions and extraordinary events might be coordinated in such a way as to successfully drive environmental and climate initiatives into public debate, which, far from being seen as residual issues that can be postponed without major political costs, eventually manage to overcome the hurdle of economic objections and ideological misgivings. To support this argument, we analyze the complex political process that Law 30754, Framework Law on Climate Change, has faced since even as early as 2008, with the first bills, until its approval in the Congress of the Republic in 2018 and its subsequent enactment by the Executive Branch.